Incidência de parasitoses humanas diagnosticadas no município de Rosário do Sul/RS - Peres, Paulo Edelvar Corrêa; Lopes, Lidiane Foletto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2010)
The human parasitoids are endemics in many regions of the country, principally where is very poor. This study aim recognize the human parasitoids with more cases that affect the population of the Rosário do Sul/RS City, and to search and to propose measures of erradication of this parasitoids. As the method was used a qualitative and quantitative research with members of community, medicals and professionals in laboratories and also with bibliographic survey. In Rosário do Sul City the parasitoids are in areas where the population have problems with basic sanitation and health education. Here we discuss potential measures to control human parasitic diseases in the affected communities, based on mass treatment, health education and eradication of vectors.